2014
DOI: 10.1002/jor.22657
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of osteogenic cell differentiation in response to bone morphogenetic protein or demineralized bone matrix in a critical sized defect model using GFP reporter mice

Abstract: We evaluated the osteoprogenitor response to rhBMP-2 and DBM in a transgenic mouse critical sized defect. The mice expressed Col3.6GFPtopaz (a pre-osteoblastic marker), Col2.3GFPemerald (an osteoblastic marker) and a-smooth muscle actin (a-SMACherry, a pericyte/myofibroblast marker). We assessed defect healing at various time points using radiographs, frozen, and conventional histologic analyses. GFP signal in regions of interest corresponding to the areas of new bone formation was quantified using a novel com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 33 publications
1
35
1
1
Order By: Relevance
“…However, the supraphysiologic doses of rhBMP used in clinical practice and the kinetics of BMP release from the carrier [2] are associated with inconsistent clinical results and several complications [3,4,5]. Previous animal studies using a mouse critical-sized femoral defect model in our laboratory have demonstrated that treatment with rhBMP-2 leads to healing of the defect, with the bony bridge gradually becoming thinner at later time points (28 and 56 days after treatment) [6]. It has been hypothesized that this thin cortical bone repair associated with rhBMP-2 treatment is secondary to the rapid release of the protein from the collagen sponge [6,7], leading to osteoclast stimulation and subsequent bone resorption.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the supraphysiologic doses of rhBMP used in clinical practice and the kinetics of BMP release from the carrier [2] are associated with inconsistent clinical results and several complications [3,4,5]. Previous animal studies using a mouse critical-sized femoral defect model in our laboratory have demonstrated that treatment with rhBMP-2 leads to healing of the defect, with the bony bridge gradually becoming thinner at later time points (28 and 56 days after treatment) [6]. It has been hypothesized that this thin cortical bone repair associated with rhBMP-2 treatment is secondary to the rapid release of the protein from the collagen sponge [6,7], leading to osteoclast stimulation and subsequent bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Previous animal studies using a mouse critical-sized femoral defect model in our laboratory have demonstrated that treatment with rhBMP-2 leads to healing of the defect, with the bony bridge gradually becoming thinner at later time points (28 and 56 days after treatment) [6]. It has been hypothesized that this thin cortical bone repair associated with rhBMP-2 treatment is secondary to the rapid release of the protein from the collagen sponge [6,7], leading to osteoclast stimulation and subsequent bone resorption. Another potential option for BMP protein delivery is ex vivo regional gene therapy [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Col2.3-GFP in particular has been widely used in lineage tracking studies to identify osteoblasts derived from various cell populations during development, adulthood, or following injury [19, 21, 6365]. They are also useful to track differentiation following transplantation of cells.…”
Section: Isolation Of Osteoblast Lineage Cells Based On the Expressiomentioning
confidence: 99%
“…Alaee used an elegant mouse model of multiple osteogeneic reporter genes and observed that although DBM had osteoinductive properties, its effect was rather limited. 8 When DBM is used as a bone filler for critical size defects, its effects are even less convincing. In rat models, for example, DBM showed significant, but limited bone formation capacity at 8 weeks.…”
Section: Introductionmentioning
confidence: 99%